Bouveret's syndrome: a strategic approach for management. Issue 2 (9th February 2021) - Taggarsi, Meghana; Lapsia, Snehal Kishore; Raymond, Thomas; Sultana, Asma
Abstract : An 81-year-old woman, diabetic and hypertensive, presented with nausea and intermittent vomiting. She had dysphagia and loss of appetite for over 6 weeks and significant weight loss over 3 weeks and was admitted in general surgery unit on emergency basis. Investigations revealed dilated stomach and a stone in first part of duodenum, with probable site of obstruction at level of first part of duodenum, secondary to a cholecystoduodenal fistula. With a preoperative diagnosis of Bouveret's syndrome, she underwent laparotomy and subtotal cholecystectomy. Postoperative recovery was delayed due to gastroparesis and delayed gastric emptying which resolved with conservative management. Successful management of this case required a multidisciplinary team approach. Early diagnosis was the key to management. Mode of treatment and management of Bouveret's syndrome should be tailored to suit patient's age, comorbidities and performance status.